Effect of Health Education Media MEGI (Coloring and Brushing Teeth) on Dental and Oral Hygiene in Elementary School Students - Regina, Ghiza Sekar; Fatimah, Siti; Herijulianti, Eliza; Putri, Rr. Megananda Hiranya (Poltekkes Kemenkes Kupang, 2023)
School-age children are one of the vulnerable groups to oral health problems, such as dental caries and gum inflammation. These issues are often caused by children's lack of understanding of the importance of maintaining oral hygiene. Providing education using engaging media can be done as an effort to enhance children's understanding of daily oral health care. This study aims to determine the influence of the MEGI (Coloring and Brushing Teeth) health education media on dental and oral hygiene in elementary school students. This research is a quasi-experimental study with a one-group pre-post-test design. The research sample consists of second-grade elementary school students selected using total sampling techniques. Education is provided using the MEGI health education media. Data collection on dental and oral hygiene is recorded using the Plaque Free Score index. Research data is analyzed with Paired T-test. The results show that the mean dental and oral hygiene of students increased between before (14.25) and after (66.14) being given education using the MEGI health education media. The Paired T-test result obtained a p-value of 0.00 < α 0.05, indicating a significant influence of the MEGI health education media on dental and oral hygiene in elementary school students. The MEGI health education media can be used as one of the counseling media options to improve dental and oral hygiene in elementary school students. For future research, it is recommended to provide continuous education to children, and oral hygiene examinations should be conducted periodically.